Poverty in Australia. [Papers by W.C. Wentworth, D.(V.) Donnison, R. Henderson a.o. Ed. by G.G. Masterman] (Angus & Robertson, 1969)
Australian Institute of Political Science. Proceedings of 35th Summer School.